Simulation analysis of rockfall movement characteristics with debris slope using Unity3D based on UAV remote sensing DSM: a case study of the G318 Highway on the Tibetan Plateau - Ye, Tangjin; Tao, Wei; Li, Hu; Zhang, Yu; Liu, Ruyuan (Frontiers in Ecology and Evolution, 2023)
Rockfalls on debris slopes pose a significant hazard to canyon roads on the Tibetan Plateau. In order to assess risks and develop effective engineering solutions, it is crucial to fully understand the characteristics and processes of rockfall movement. This research utilizes UAVs and three-dimensional (3D) laser scanners to capture images and data, while Pix4D is employed to create a high-precision 3D model from the collected data. Unity3D is utilized to analyze the movement characteristics and deposition positions of rockfall. Various movement characteristic indexes, such as velocity, acceleration, displacement, energy loss, and deposit position, are computed and examined for blocks with different shapes, sizes, instability types on the debris slope, and blocks composed of various slope materials and inclinations. The aim is to obtain insights into the specific movement mechanisms of debris slopes, which differ from conventional slopes. Field experiments have confirmed the effectiveness of the Unity3D simulation approach. Building upon this foundation, a high-precision 3D simulation model for the debris slope of the G318 Highway on the Tibetan Plateau is developed using Unity3D. This model is used to calculate the movement characteristics, energy variation, and deposition positions of rockfall. The findings are then compared with those of common models. The results demonstrate that the high-precision 3D simulation model computed by Unity3D provides more accurate and reasonable results compared to the common model. Moreover, the movement characteristics, energy variation, and deposition positions of rockfall on debris slopes exhibit specific characteristics. By employing Unity3D simulation analysis, a comprehensive understanding of the phenomena and behavior of rockfall on debris slopes can be achieved, enabling the proposal of more reasonable engineering protection measures.